Overview of the Structural Behavior of Columns, Beams, Floor Slabs and Buildings during the Earthquake of 2016 in Ecuador - Castañeda, Ángel Emilio; Mieles Bravo, Yordy (Revista Ingeniería de Construcción, 2017)
This paper analyzes different types of failures in buildings of the cities of Portoviejo, Manta and Bahía de Caráquez during the earthquake of April 16, 2016. The evidence derived from the failures refer to existing codes and design considerations in order to reveal how modeling corresponds or not with different reinforcedconcrete columns, floor slabs and rigid frame buildings without structural walls. Given the diversity of constructive solutions found in the steel-deck slabs, a 23 factorial experiment design was performed to identify the influence and independence of the type of node, the rectangularity of the floor plan and the height of buildings on the strength and deformation parameters of floor slabs, in relation to the failures observed. Additionally, this paper undertakes a singular analysis approach of different failure causes in a building demolished in the city of Portoviejo, based on evidence revealed by the earthquake, and described some of the distinctive features of this type of study.